Can behavioural change interventions improve self-efficacy and exercise adherence among people with Parkinson’s? A systematic review protocol [version 2; peer review: 2 approved] - Dr Ruth McCullagh; Leanne Ahern; Prof Sarah E Lamb; Prof Suzanne Timmons (HRB Open Research, 2022)
Background: People with Parkinson’s (PwP) have a higher tendency to adopt sedentary lifestyle behaviours and have lower physical activity levels compared to their healthy peers. Previous research has indicated that personal factors including poor outcome expectation and low self-efficacy are stronger predictors of exercise adherence than disease severity.: The purpose of this review is to synthesize the best available evidence on interventions that encompass self-management strategies to overcome barriers to exercise and improve self-efficacy and exercise adherence among PwP. Methods: The following databases will be searched using a comprehensive search strategy: EBSCO, Medline, CINAHL, Web of Science, PubMed, Embase, Scopus, Google Scholar and Cochrane Library from database inception to 2020. Interventional studies including behavioural change interventions will be included in this review. The title, abstract and full-text screening will be conducted by two independent reviewers. The Joanne Briggs Institute Checklist will be used to assess the quality of each included study. Data will be extracted by two independent reviewers. The outcomes of interest will be self-efficacy outcomes and measures of exercise adherence. A systematic narrative synthesis will be conducted using a framework analysis, applying the Theoretical Domains Framework and Behaviour Change Wheel, producing findings focusing on practice-orientated outcomes. Presentation of data will include tables and text summarizing the characteristics and findings of the eligible studies. Data synthesis and statistical analysis will be performed in Review manager 5.3. The quality of evidence will be reviewed using the GRADE criteria. Discussion: The review will comprehensively synthesize the  available evidence on interventions to enhance self-efficacy, improve quality of life, physical function,  ultimately improving exercise adherence among PwP and provide invaluable information for healthcare professionals.. This review will make recommendations for appropriate self-management strategies for maximum effect and may have implications for policy and practice regarding enhancing self-efficacy and long-term exercise adherence among PwP.